Effectiveness of Training in Improving Human Resource Competency - Neneng Hayati; Erwin Yulianto (Institut Pendidikan Indonesia, 2021)
Human resources in the company play a role in determining the company's success in achieving the expected results. Human resources in a company need to be managed professionally so that there is harmony between employee competence and the company's demands and goals. One process of developing and increasing employee competency can be carried out by carrying out education and training activities. Training for employees can be carried out in various ways, including on-the-job training and off-the-job training. With training, it is hoped that employee productivity will increase and they will be able to work more effectively and efficiently, especially for challenges in achieving company goals in the future. Training evaluation is one way to measure the effectiveness of training so as to provide feedback for the company in order to improve human resource competence.